2022
DOI: 10.1038/s41598-022-16865-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between acetabular dysplasia and sagittal spino-pelvic alignment in a population-based cohort in Japan

Abstract: The relationship between acetabular dysplasia and spino-pelvic alignment remains unclear. The aim of this study was to clarify the association between acetabular dysplasia and spino-pelvic alignment, based on a large-scale population-based cohort in Japan. From the third survey of the Research on Osteoarthritis/Osteoporosis Against Disability (ROAD) study, 1,481 participants (491 men and 990 women; mean age, 65.3 years) were analyzed. Center-edge (CE) angle and spino-pelvic parameters (lumbar lordosis, LL; sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…A close relationship between degenerative conditions of the hip and spine was already described by Offerski and MacNab as early as 1983 [24]. Harada et al recently conducted a study investigating spinopelvic alignment in patients with hip dysplasia and found that patients with this condition had a significantly higher pelvic incidence (PI) than patients without [25]. Abola et al showed, in a cadaver study, that a high PI was associated with changes in sacral anatomy, which subsequently also affected the sacroiliac joint [26].…”
Section: Discussionmentioning
confidence: 84%
“…A close relationship between degenerative conditions of the hip and spine was already described by Offerski and MacNab as early as 1983 [24]. Harada et al recently conducted a study investigating spinopelvic alignment in patients with hip dysplasia and found that patients with this condition had a significantly higher pelvic incidence (PI) than patients without [25]. Abola et al showed, in a cadaver study, that a high PI was associated with changes in sacral anatomy, which subsequently also affected the sacroiliac joint [26].…”
Section: Discussionmentioning
confidence: 84%
“…Although patients with a high PI may experience a similar pathophysiology as those with acetabular dysplasia, recent studies have found they are not significantly associated. 17 While outside the scope of the present study, the contributions of acetabular and/or femoral version are similarly becoming increasingly recognized as important factors in patients with FAI. 1,30 Cumulatively, these findings indicate that the hip should not be treated in isolation, but rather in conjunction with the entire spinopelvic complex.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of PT on acetabular orientation has recently received great attention [ 34–36 ]. Studies suggest that patients with dysplasia have increased lumbar lordosis and sacral slope, leading to an increase in anterior coverage [ 17 , 37 , 38 ]. Differences in PT affect joint contact pressure and may thereby influence joint degeneration [ 39 ].…”
Section: Discussionmentioning
confidence: 99%